Chromophobe adenoma of the pituitary with Cushing's syndrome and skin pigmentation. Issue 646 (August 1979) - Sterling, N.; Hall, M. R.
Abstract : A 76-year-old man with pigmentation and Cushing's disease is described, who was found to have a large chromophobe adenoma of the pituitary. Despite normal skull X-rays the presence of bitemporal hemianopia led to the diagnosis which was later confirmed at post-mortem. Adrenalectomy performed in the treatment of Cushing's disease may be followed by skin pigmentation and an enlarging pituitary tumour (Nelson's syndrome), changes which are commonly attributed to the removal of the negative feed-back mechanism. The spontaneous occurrence of these changes in this patient who did not undergo adrenalectomy supports the view that a pituitary tumour pre-exists in cases of Nelson's syndrome and emphasizes the importance of directing initial treatment to the pituitary.